A new 3D pillar‐layered Cd(II) compound: Luminescence sensing property for detection of Fe3+ ions and treatment activity on focal cerebral ischemia/reperfusion. Issue 10 (4th June 2021) - Wang, Zhi; Ye, Ming; Huang, Ya‐Yi; Hu, Fang; Qi, Feng; Li, Dong
Abstract: A new Cd(II) compound, also known as [Cd2 (L2 )2 ] n ∙ x (solvent) (1 H2 L = 5‐(4‐pyridyl)‐methoxylisophthalic acid), has been facilely manufactured via the hydrothermal self‐assembly reaction of Cd(NO3 )·4H2 O and H2 L. Single‐crystal X‐ray diffraction analysis demonstrated that compound 1 displays a three‐dimensional pillar‐layered structure with the one‐dimensional opened passageway filled by lattice water molecules. Investigations of luminescent properties indicated that compound 1 discharges strong blue luminescence at normal temperature, and the solvent‐free samples of 1a can be served as a luminescent sensor for the probe of Fe 3+ ions in the aqueous solution with highly selective reactions and hypersensitivity. Moreover, the treatment activity of the compound on focal cerebral ischemia/reperfusion was evaluated, and the specific mechanism was explored at the same time. The western blotting assay was conducted to assess the expression levels of the AQP4 protein in the brain tissue around ischemia. Besides, the activation of the superoxide dismutase was evaluated using enzyme‐linked immunosorbent assay by measuring the content of the maleic dialdehyde and superoxide dismutase in the cerebrospinal fluid. The Cell Counting Kit‐8 was used to determine the inhibitory activity of the compound on HMEC‐1 human microvascular endothelial cells. Abstract : A new Cd(II) compound has been prepared, and luminescent investigations indicated that it could be served as a luminescent sensor for the probe of Fe 3+ ions in the aqueous solution. Moreover, the treatment activity of the compound on focal cerebral ischemia/reperfusion was evaluated and the specific mechanism was explored at the same time.